A “giant bomb” in acute myocardial infarction due to coronary artery aneurysm: a case report - Chen, Jin; Du, Wei; Jiang, Jianyu; Xu, Liugang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary artery aneurysm associated with acute coronary syndromes represents a rare clinical entity, particularly in cases with persistent significant thrombus burden following aspiration therapy. The novel pathomechanism of intra-aneurysmal thrombosis secondary to pathological flow dynamics—characterized by endothelial shear stress perturbation and blood stasis—has been rarely documented. While existing literature describes therapeutic applications of surgical repair, percutaneous intervention, and pharmacotherapy in coronary artery aneurysm management, no consensus-driven protocol has been established, reflecting critical knowledge gaps in risk-stratified treatment algorithms for thrombus-laden aneurysms.Case outlineA 51-year-old female presenting with acute ST-segment elevation myocardial infarction underwent emergency coronary angiography, revealing a large right coronary artery aneurysm with significant intra-aneurysmal thrombus burden. Despite successful thrombus aspiration restoring distal TIMI 3 flow, persistent residual thrombus within the aneurysmal segment prompted the selection of intensified anticoagulation combined with dual antiplatelet therapy over percutaneous intervention. Throughout the therapeutic course, the patient remained asymptomatic without recurrent angina. Follow-up angiography performed after 7 days of targeted antithrombotic therapy demonstrated near-complete resolution of the intra-aneurysmal thrombus, accompanied by preserved coronary flow and no evidence of distal embolization.ConclusionWe present a rare case of ST-segment elevation myocardial infarction complicated by a coronary artery aneurysm, highlighting the therapeutic challenges in managing such complex pathologies. While intensified anticoagulation combined with dual antiplatelet therapy constitutes a clinically valid approach, the absence of consensus guidelines results in significant variability in treatment protocols. This case underscores the urgent need for large-scale multicenter studies to establish evidence-based management strategies for patients with coronary artery aneurysm associated with acute coronary syndromes.